Accesibilidad al microcredito y su contribución en el desarrollo de las micro empresas ubicadas en la comuna tres de la ciudad de Cali (2021)
This research seeks to determine the conditions of access to microcredit and its contribution to the development of microenterprises in commune three of the city of Cali in Colombia. It also seeks to know the profile of microentrepreneurs, identify the perception regarding the conditions of access to microcredit and measure the contribution of microcredit in the development of microenterprises in the commune from the perspective of microentrepreneurs.